(untitled) (Journal of Asian Development Studies, 2026)
Tourism, particularly eco-tourism, promotes long-term development by supporting local economies while protecting ecosystems and culture.It also acts as a conservation catalyst, raising awareness aboutbiodiversity and encouraging environmental stewardship. It promotes a greater understanding of nature through educational programs and programs, boosting support for conservation projects. This research investigates tourism’s cultural, ecological, and socioeconomic ramifications from the viewpoint of the indigenous population in Dir, Khyber Pakhtunkhwa, Pakistan. A survey on ecotourism’s socioeconomic impact involved 180 respondents across ten high-potential communities. Reliability was ensured using Cronbach’s alpha coefficient. Varimax rotation clarified key findings: strong support (loading factor: .990) for population increase. Concerns included rising standard of living (loading factor: .776) and seasonal employment (loading factor: .819). Consensus (loading factor: .962) favored environmental conservation and community-based business opportunities. It also recommends robust policies, infrastructure investments, targeted marketing, community engagement, visitor facilitation, and hospitality among localsto promote tourist return visits